Nazca como estado Un análisis a los elementos del estado en la cultura Nazca - Aceituno Colquehuanca, Erick Brayhan (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
This essay demonstrateswhy the Nazca culture should be considered a State, and for this a deductive historical investigationwas carried outin which it was possible tofind very important and relevant information that helpedus inthe development of this writing, based onthe concepts and elements that make up a State to make a comparison and articulate it to the Nazca culture, consequently it was possible to identify that the Nazca culture possessedterritory, population and power, it was also and isrich in great architectural constructions such as its hydraulic aqueducts that are recognized by all. , or its great pottery and textiles. It wasconcluded that the Nazca culture should be considered a State, because even in the oldesttimes there was already a political, social, and other organization.